On optimization over a polyhedral set and Augmented Lagrangians. - Hendrix, Eligius María Theodorus; Guerrero-García, Pablo; Rocha, Ana Maria A.C. (Kungliga Tekniska högskolan, 2025)
Linear constraints have a long tradition in optimization problems. It means that the feasible set is a polyhedral set or can be described as a polytope. In Global Optimization,we use the characteristics to derive specific algorithms. In our contribution,wewill focus on the so-called Augmented Lagrangian approach where constraints are captured in Lagrangian terms and penalties.We show some first numerical analysis with the easiest case of having a linear objective.
Keywords: Lagrange, Funciones de; Programación lineal; Polyhedral set; Augmented Lagrangian; Linear programming